2006
DOI: 10.3989/gya.2006.v57.i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antibacterial and surface activity of 1,2,4-triazole derivatives

Abstract: Síntesis y propiedades antibacterianas y tensoactivas de derivados 1,2,4-triazólicos Es interesante el uso del 1-(4-amino-5-mercapto-4H-[1,2,4]triazol-3-il)heptadecano-1-sulfonato sódico (2) como un nuevo precursor en la síntesis de compuestos heterocíclicos biológicamente importantes. La reacción de 2 con disulfuro de carbono en piridina y cloruros de acilo rindió derivados 1,2,4-triazólicos. Condensación de 2 con aldehídos apropiados produjo 5a-c que ciclaron por tratamiento con ácido tioglicólico para dar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The results indicated that the compound was highly active against selected pathogens (El-Sayed, 2006).…”
mentioning
confidence: 98%
“…The results indicated that the compound was highly active against selected pathogens (El-Sayed, 2006).…”
mentioning
confidence: 98%
“…2 She had an uneventful anaesthetic history and no allergies. Her airway, cardiorespiratory and neurological examinations were all normal.…”
mentioning
confidence: 99%
“…Unsubstituted and 3-substituted-7-aryl-5H-6,7-dihydroimidazo [2,1- 44 . Some 1,2,4-triazole derivatives (23, 24) had shown inhibitory activity against some bacteria 45,46 . Some 1,2,4-triazole derivatives (25) were showed antibacterial activity 47 .…”
Section: Antimicrobial and Antifungal Activitymentioning
confidence: 99%